2016
DOI: 10.1097/mpg.0000000000000907
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Protects Against Gastrointestinal Symptoms in Infants at High Risk for Autism During Early Development

Abstract: Objectives Parents of children with Autism spectrum disorders (ASD) often report gastrointestinal dysfunction in their children. The objectives of the current study were to: 1) determine if infants at high risk for developing ASD (i.e. siblings of children diagnosed with ASD) show greater prevalence of gastrointestinal problems, and 2) whether this prevalence is associated with diet and age at weaning from breast milk. Methods Using questionnaires, diet history and gastrointestinal problems were tracked pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
0
13
1
4
Order By: Relevance
“…reported an increased risk of ASD associated with suboptimal breast‐feeding practices . Also, late weaning and exclusive breast‐feeding were found to be associated with fewer GI symptoms in high‐risk infants (siblings of children diagnosed with ASD), in a study in which GI dysfunction was defined as part of an ASD endophenotype . The present study did not evaluate breast‐feeding practices, but the duration of exclusive breast‐feeding and of any breast‐feeding did not differ between the ASD and control groups.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…reported an increased risk of ASD associated with suboptimal breast‐feeding practices . Also, late weaning and exclusive breast‐feeding were found to be associated with fewer GI symptoms in high‐risk infants (siblings of children diagnosed with ASD), in a study in which GI dysfunction was defined as part of an ASD endophenotype . The present study did not evaluate breast‐feeding practices, but the duration of exclusive breast‐feeding and of any breast‐feeding did not differ between the ASD and control groups.…”
Section: Discussioncontrasting
confidence: 53%
“…40 Also, late weaning and exclusive breast-feeding were found to be associated with fewer GI symptoms in high-risk infants (siblings of children diagnosed with ASD), in a study in which GI dysfunction was defined as part of an ASD endophenotype. 41 The present study did not evaluate breast-feeding practices, but the duration of exclusive breast-feeding and of any breast-feeding did not differ between the ASD and control groups. Further studies are need to investigate the association between feeding practices and ASD, and the protective effects of breast-feeding and breast-milk with regard to ASD.…”
Section: Discussionmentioning
confidence: 58%
“…and production of short-chain fatty acids may increase the water content in faecal mass, but also stimulate gastrointestinal motor complex activity; 3) probably HMOs bind water, thus increase its content in faeces [34]. Scientific research has shown that long exclusive breastfeeding is a protective factor against gastrointestinal dysfunction, including constipation in children at high risk of developing autism spectrum disorder [35]. However, no attempts have been made to verify the suitability of orally administered breast milk in the immediate treatment of abnormal rhythm of bowel movements, especially in different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…1 Our comparisons of such infants with age-matched “low-risk” infants who have an older sibling without autism spectrum disorder allows for the identification of putative biomarkers of this disorder. 2 Although vaccination behaviors were not our primary focus, studies showing decreased rates of vaccination against measles–mumps–rubella (MMR) among high-risk infants prompted us to analyze available data on vaccination behaviors in our sample of 206 families from southern California (71 of which had a child with autism spectrum disorder and 135 that did not have a child with autism spectrum disorder) (Table 1). 3,4 …”
Section: To the Editormentioning
confidence: 99%